2004
DOI: 10.1074/jbc.m404428200
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Co-activator p/CIP (NCoA-3) Is Up-regulated by STAT6 and Serves as a Positive Regulator of Transcriptional Activation by STAT6

Abstract: Transcriptional activation by signal transducer and activator of transcription 6 (STAT6) has been shown to require the direct interaction not only with co-activators such as p300 and cAMP-responsive element-binding protein-binding protein (CBP) but also with nuclear coactivator 1, a member of the p160/steroid receptor coactivator family. Among the p160/steroid receptor coactivators, only p/CIP (nuclear co-activator 3) has been shown to be up-regulated by interleukin (IL)-4 in B cells through a STAT-6-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 52 publications
1
42
0
Order By: Relevance
“…This is consistent with earlier data demonstrating different binding affinities of STAT6 for the ε (high affinity) and g1 (low affinity) promoter (27). Control PCRs diagnosing promoter regions of IgG2a (Ig2a) and of a proteasome gene, (Pr) (21,22), which lack STAT6 binding sites, did not generate signals (Fig. 4A, 4B).…”
Section: Efficient Stat6 Binding and Prevention Of Bcl6 Binding To I«supporting
confidence: 80%
“…This is consistent with earlier data demonstrating different binding affinities of STAT6 for the ε (high affinity) and g1 (low affinity) promoter (27). Control PCRs diagnosing promoter regions of IgG2a (Ig2a) and of a proteasome gene, (Pr) (21,22), which lack STAT6 binding sites, did not generate signals (Fig. 4A, 4B).…”
Section: Efficient Stat6 Binding and Prevention Of Bcl6 Binding To I«supporting
confidence: 80%
“…Although p160/SRC family coactivators NcoA-2 and p/CIP are closely related to SRC-1, and known to interact with CBP/p300, they do not directly interact with STAT6 (17). However, p/CIP mRNA and protein levels are up-regulated by IL-4, and p/CIP enhances IL-4 transcriptional responses through still an unknown mechanism that involves interaction with p300 (20). Thus, STAT6 employs several coactivator proteins through both direct and indirect interactions in recruiting CBP/p300 and basal transcriptional machinery to IL-4-responsive promoters.…”
Section: Discussionmentioning
confidence: 99%
“…SRC-1 functions as a coactivator for STAT6, as well as for STAT3 (18) and STAT5 (19). Also another member of the p160/ SRC family coactivators p/CIP (NcoA-3) indirectly interacts with STAT6 via p300 (20).…”
mentioning
confidence: 99%
“…There is evidence for a role played by NRF1 in regulating the expression of CXCR4 (19). NCOA3 and PRDM2 have been reported to be transcriptional co-activators (20,21), and Munier et al (22) have suggested that NCOA3 can interact with the HIV-1 LTR. STXBP2 is an interactor of SYNTAXIN 3, which acts on the membrane function and processes of the cell (23); however, it is unclear how knockdown of STXBP2 (directly or indirectly) affects the amount of reverse transcribed HIV-1 proviral DNA.…”
Section: Resultsmentioning
confidence: 99%